Performance of rice blast resistance genes in multi-environment tests in India - M. SRINIVASPRASAD; R. SRIDHAR, K. MURALIDHARAN*, D. KRISHNAVENI, G.S. LAHA, C.S. REDDY (Indian Phytopathology, 2004)
Rice genotypes carrying resistance genes to blast disease were evaluated in multi-environment tests (METs). Tadukan carrying resistance gene Pi-ta showed small lesions infecting <2% leaf area indicating a very high level of durable resistance to blast disease. The METs clearly demonstrated the expression of a high degree of resistance in A57 carrying three resistance genes (Pi-1, Pi-2 and Pi-4). A57 was identified as the best line that exhibited resistance to blast across the country in all rice growing environments, irrespective of ecosystems. The performance of BL 245 with two resistance genes (Pi-2 and Pi-4) and C101LAC (Pi-1) was comparable to A57. The performance of these NILs was marginally superior to the resistant checks (Tadukan, Rasi, Tetep and IR 64) and the international blast differential Raminad Strain 3. Alleles for the genes identified as effective and durable in the METs in this study must be located in our cultivars besides discovering newer ones to effectively utilize resistance genes in future.